2020
DOI: 10.20944/preprints202002.0302.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

“Look at Me, I Plan to Quit Smoking”: Bayesian Hierarchical Analysis of Adolescent Smokers’ Intention to Quit Smoking

Abstract: The tobacco epidemic is one of the leading public health threats the world has ever faced and public health policy that seeks to limit the problem may not only have to target the price of tobacco but also the initiation stage in a smoker’s life – the adolescent stage. This research contributes to the health economics literature by using a Bayesian hierarchical logistic model, estimated using Hamiltonian Monte Carlo (HMC) methods to empirically identify what drives the intentions to quit smoking among adolescen… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Of the 116 respondents, 81 (69.8%) of them had smoked and 56% of them had quit smoking [26]. Another study stated that the level of knowledge of the youth of Mx Club Samarinda 135 about the dangers of smoking to health was included in the good category, which was 25 respondents (83.3%) [27]. This was in line with a study that showed a significant relationship between the level of knowledge and motivation to quit smoking in former smokers in the pulmonary section of the RSU (General Hospital) Siloam Lippo Village [28].…”
Section: Discussionmentioning
confidence: 99%
“…Of the 116 respondents, 81 (69.8%) of them had smoked and 56% of them had quit smoking [26]. Another study stated that the level of knowledge of the youth of Mx Club Samarinda 135 about the dangers of smoking to health was included in the good category, which was 25 respondents (83.3%) [27]. This was in line with a study that showed a significant relationship between the level of knowledge and motivation to quit smoking in former smokers in the pulmonary section of the RSU (General Hospital) Siloam Lippo Village [28].…”
Section: Discussionmentioning
confidence: 99%